1993
DOI: 10.1002/art.1780361010
|View full text |Cite
|
Sign up to set email alerts
|

Association between reactive arthritis and antecedent infection with shigella flexneri carrying a 2‐md plasmid and encoding an hla–b27 mimetic epitope

Abstract: Objective. To determine whether Shigellaflexneri strains that cause enteric infection and are associated with reactive arthritis (ReA) carry a 2-Md plasmid, pHS-2, which encodes an HLA-B27 mimetic epitope.Methods. Plasmid DNA from Shigella isolates was characterized by DNA-DNA hybridization, restriction endonuclease digestion, and sequencing.Results. S jlexneri strains associated with ReA carried a 2-Md plasmid homologous to pHS-2.Conclusion. The finding of pHS-2 in additional Shigella strains associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1
3

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 6 publications
0
12
1
3
Order By: Relevance
“…Shigella DNA has not been convincingly demonstrated in the joints of ReA patients, making it more likely that only pieces of bacteria are transported to the joints. It has been reported that only Shigella strains containing the pHS-2 plasmid are arthritogenic (180,191). pHS-2 influences invasiveness and intracellular and intercellular movement and hence is important for the mechanism of infection.…”
Section: Bacterium-host Interactionmentioning
confidence: 99%
“…Shigella DNA has not been convincingly demonstrated in the joints of ReA patients, making it more likely that only pieces of bacteria are transported to the joints. It has been reported that only Shigella strains containing the pHS-2 plasmid are arthritogenic (180,191). pHS-2 influences invasiveness and intracellular and intercellular movement and hence is important for the mechanism of infection.…”
Section: Bacterium-host Interactionmentioning
confidence: 99%
“…We know that there are more than 100 subsets of HLA B27 9 and we know the amino acid sequence for each of the B27 subsets. We know that there are specific infections like Salmonella 10 and Shigella 11 that trigger reactive arthritis. There is even sex to intrigue the reader of this mystery novel since we know that non-gonococcal urethritis is a clear trigger for reactive arthritis 12 .…”
Section: Introductionmentioning
confidence: 99%
“…84-86 It was found that Shigella flexneri strains that are isolated from ReA patients carry a plasmid (pHS-2) 86. DNA sequence analyses of this plasmid revealed that it contains an open reading frame (ORF) encoding a 22 amino acid peptide with sequence homology to B27, again involving the sequence QTDR—that is, GTVCAQTDRHSLSCIAMQ.…”
Section: Resultsmentioning
confidence: 99%